JIWA PUITIS NENEK MOYANG ORANG BUTON DI RUMAH TRADISIONAL BUTON MALIGE KOTA BAUBAU SULAWESI TENGGARA - Muhammad Zakaria Umar (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
Our ancestors have poetic spirit in architecture. This study aims at assessing the poetic spirit of Butonese ancestors to the traditional houses namely Malige. The research was a qualitative descriptive approach. The results of this study indicate that the ancestors of Butonese have poetic spirit in making their traditional house, Malige. Keywords: Poetic soul, the ancestors of Buton, Malige